The Autonomous Learning in Supporting Communication On Board in 5.0 Era (A Study Case of Young Cadets’ ELL at PIP Makassar) - Novianty Palayukan; Sunarlia Limbong; Edi Wahyono; Nurul Hatifah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the role of tablet-assisted autonomous learning in improving Maritime English proficiency for on-board communication among young cadets at PIP Makassar in the 5.0 Era. It aims to measure young cadets’ levels of autonomous learning, identify barriers, and explore applied strategies. A mixed-method design was employed, combining quantitative data from 141 young cadets collected using the Self-Directed Learning Readiness Scale (Fisher & King, 2010) with qualitative insights from semi-structured interviews. The results indicate that 98 (69.5%) of young cadets demonstrated a high level of autonomy and 43 (30.5%) a moderate level, with desire for learning emerging as the strongest factor, followed by self-control and self-management. Major barriers included limited tablet specifications, unstable campus Wi-Fi, and heavy academic schedules. Nevertheless, young cadets employed strategies such as reading e-books, listening to English songs, and reviewing materials during optimal times. These strategies primarily supported receptive skills (reading and listening), consistent with Krashen’s Input Hypothesis. The findings contribute to maritime education literature by highlighting that while technology promotes learner autonomy, its effectiveness depends on institutional support through device enhancement, reliable internet access, and flexible study arrangements.